A Research Paper on Digital Marketing Communication and Consumer Buying Decision Process: An Empirical Study in the Indian Passenger Car Market. Issue 2 (15th March 2018) - Dahiya, Rekha, Gayatri
ABSTRACT: The effect of digital marketing communication on product categories like books, music, fashion accessories, clothing, banking and online gaming etc. has been well researched by the researchers; but automobile industry despite being one of the largest digital spenders has faced dearth of academic studies especially in India. The present study aims to understand the effect of digital marketing communication on consumer buying decision process in Indian passenger car market. Mixed methodology was adopted for the study. Primary data was collected from 784 respondents from 'Delhi' using area wise proportionate sampling. One sample Wilocoxon Signed Rank, one sample binomial test and chi-sqaure tests were applied as tests of significance. The study concluded that 75% of the respondents used at least one digital channel of communication while buying a car. 'Website' was the most used digital channel of communication while buying a car followed by 'social networking sites' and 'smartphones'. Each and every stage of car buying decision making process right from 'need recognition' to 'post purchase' was 'significantly' affected from digital marketing communication with 'evaluation' being the most affected stage. The results of the study confirmed that digital marketing communication is capable of even triggering need recognition in high involvement product category like car. The results also established that consumers feel positive towards digital communication, get affected from other customers' reviews and express their post-purchase feeling feelings over digital platforms. However, the study also confirmed that although customers appreciate the usage of digital channels throughout the decision making journey, still they don't book a car online.